Player responses to match and training demands during an intensified fixture schedule in professional rugby league: A case study - Twist, C.; Highton, J.; Daniels, M.; Mill, N.; Close, G. (International Journal of Sports Physiology and Performance, 2017)
Player loads and fatigue responses are reported in 15 professional rugby league players (24.3 ± 3.8 y) during a period of intensified fixtures. Repeated measures of internal and external loads, perceived well-being, and jump flight time were recorded across 22 d, comprising 9 training sessions and matches on days 5, 12, 15, and 21 (player exposure: 3.6 ± 0.6 matches). Mean training loads (session rating of perceived exertion × duration) between matches were 1177, 1083, 103, and 650 AU. Relative distance in match 1 (82 m/min) and match 4 (79 m/min) was very likely lower in match 2 (76 m/min) and likely higher in match 3 (86 m/min). High-intensity running (=5.5 m/s) was likely to very likely lower than match 1 (5 m/min) in matches 2-4 (2, 4, and 3 m/min, respectively). Low-intensity activity was likely to very likely lower than match 1 (78 m/min) in match 2 (74 m/min) and match 4 (73 m/min) but likely higher in match 3 (81 m/min). Accumulated accelerometer loads for matches 1-4 were 384, 473, 373, and 391 AU, respectively. Perceived well-being returned to baseline values (~21 AU) before all matches but was very likely to most likely lower the day after each match (~17 AU). Prematch jump flight times were likely to most likely lower across the period, with mean values of 0.66, 0.65, 0.62, and 0.64 s before matches 1-4, respectively. Across a 22-d cycle with fixture congestion, professional rugby league players experience cumulative neuromuscular fatigue and impaired match running performance.